The Faddeev equation and essential spectrum of a Hamiltonian in Fock space - Muminov, M. I.; Rasulov, T. H. (Methods of Functional Analysis and Topology, 2011)
A Hamiltonian (model operator) H associated to a quantum system describing three particles in interaction, without conservation of the number of particles, is considered. The Faddeev type system of equations for eigenvectors of H is constructed. The essential spectrum of H is described by the spectrum of the channel operator.